Comparison of dermabond adhesive glue with skin suture for repair of episiotomy - Chamariya, Sumit; Prasad, Madhva; Chauhan, Anahita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective of the study was to compare perineal skin closure of episiotomy with cyanoacrylate adhesive glue with standard skin closure. Methods: A prospective randomized controlled study was conducted in a tertiary care hospital. 100 primigravidae undergoing normal vaginal delivery were assigned to study and control groups. After completion of vagina mucosa and muscle suturing; in study group, skin closure was done with adhesive glue and in control group, conventional suturing done. Time taken to complete skin closure, pain perceived during and after procedure and postoperative wound healing and cosmesis of perineal area were studied. Results: The mean time for skin closure with adhesive glue (1.16 minutes) was lesser than conventional skin suturing (3.52 minutes). 84% of study group patients perceived no pain (VAS score of 1) while 72% of patients in control group perceived mild pain during suturing. In all time intervals (during and after the procedure), pain intensity was lower in the study group (p value <0.05). The time for healing was around 4 days in the study group and around 8 days in the control group. There was no statistically significant difference in the rate of wound complications and cosmesis between the groups. Conclusions: Findings of the study support the safe and efficacious usage of cyanoacrylate adhesive glue for episiotomy skin closure. Cyanoacrylate adhesive glue is a superior alternative to conventional skin suturing shorter time, less pain during and after the procedure. Wound healing and cosmesis are comparable with both adhesive glue and suturing.